Effect of anterior dental caries on psychological behavior and quality of life of Saudi pediatric patients - Rafi Ahmad Togoo; Hanan Qasem Alfaifi; Fatimah Mohammed Algarny; Jamilah Dafer Alahmari; Raghad Ayed Ali AlQhtani; Hanin Ahmed Asiri (Wolters Kluwer Medknow Publications, 2022)
Introduction: Dental caries is the most common chronic infectious disease involving children and toddlers. Carious invasion of anterior teeth causes infection, pain, compromised speech, mastication, and impacts the esthetics and appearance of the child. Dental caries' immediate and long-term effects affect the child's quality of life and his family, leading to significant social, economic, and psychological consequences. Aim: The present study was conducted to evaluate the effect of anterior dental caries on Saudi pediatric patients' psychological behavior and quality of life. Materials and Methods: A self-administered, structured questionnaire was used to assess the demographic variables, the prevalence of dental caries (anterior teeth), and their psychological effects on children. The data obtained were subjected to statistical analysis using IBM SPSS version 20.0 software. Results and Discussion: Five hundred and twenty-two children were included in the study, out of which 67.62% were affected with anterior carious lesions, with a mean age of 4.90 ± 1.981 years. Most parents reported that their child has anterior carious lesions, with 50% of children having toothache and 49% difficulty in eating food, especially sweets. Affected children showed psychological issues as they avoided playing, hesitated to smile, were introverted, and covered their faces while smiling. Conclusion: A high anterior dental caries prevalence and the resultant effect on psychological behavior and quality of life were observed among young children in Saudi Arabia. Enhanced educational, counseling, and preventive programs among parents and children will reduce dental caries incidence and ensure young children have a good quality of life.